Mathematical modeling of hydrolithosphere processes taking into account the processes in "wells" - I. M. Pershin; V. A. Nosova; V. V. Tsapleva (Современная наука и инновации)
The paper considers a mathematical model of the hydrolithospheric process, taking into account the "well" formed by a production well. A description of the mathematical model of the interaction of hydrolithospheric processes in the "well" with aquifers is given. The results of numerical modeling of hydrolithospheric processes show a significant influence of the “well” radius on the level decrease in the aquifer.